UPb detrital zircon ages from some Neoproterozoic successions of Uruguay: Provenance, stratigraphy and tectonic evolution. (November 2016) - Pecoits, Ernesto; Aubet, Natalie R.; Heaman, Larry M.; Philippot, Pascal; Rosière, Carlos A.; Veroslavsky, Gerardo; Konhauser, Kurt O.
Abstract: The Neoproterozoic volcano-sedimentary successions of Uruguay have been the subject of several sedimentologic, chrono-stratigraphic and tectonic interpretation studies. Recent studies have shown, however, that the stratigraphy, age and tectonic evolution of these units remain uncertain. Here we use new UPb detrital zircon ages, combined with previously published geochronologic and stratigraphic data in order to provide more precise temporal constraints on their depositional age and to establish a more solid framework for the stratigraphic and tectonic evolution of these units. The sequence of events begins with a period of tectonic quiescence and deposition of extensive mixed siliciclastic-carbonate sedimentary successions. This is followed by the development of small fault-bounded siliciclastic and volcaniclastic basins and the emplacement of voluminous granites associated with episodic terrane accretion. According to our model, the Arroyo del Soldado Group and the Piedras de Afilar Formation were deposited sometime between ∼1000 and 650 Ma, and represent passive continental margin deposits of the Nico Pérez and Piedra Alta terranes, respectively. In contrast, the Ediacaran San Carlos (<552 ± 3 Ma) and Barriga Negra (<581 ± 6 Ma) formations, and the Maldonado Group (<580–566 Ma) were deposited in tectonically active basins developed on the Nico Pérez and Cuchilla Dionisio terranes, and the herein defined Edén Terrane. The Edén and the Nico Pérez terranes likely accreted at ∼650–620 Ma (Edén Accretionary Event), followed by their accretion to the Piedra Alta Terrane at ∼620–600 Ma (Piedra Alta Accretionary Event), and culminating with the accretion of the Cuchilla Dionisio Terrane at ∼600–560 Ma (Cuchilla Dionisio Accretionary Event). Although existing models consider all the Ediacaran granites as a result of a single orogenic event, recently published age constraints point to the existence of at least two distinct stages of granite generation, which are spatially and temporally associated with the Edén and Cuchilla Dionisio accretionary events. Highlights: A new tectono-stratigraphic scheme for the Neoproterozoic of Uruguay is proposed. The scheme relies on new and previously published UPb detrital zircon ages. Tectonomagmatic activity during the Tonian-Cryogenian is absent in the Nico Pérez Terrane. The Ediacaran is punctuated by extensive tectonomagmatic activity in all the domains. These stages are characterized by either passive continental margins or fault-bounded basins.